2006
DOI: 10.1086/504812
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Infection after Transplantation: A Review of 98 Cases

Abstract: PVB19 is a rare but clinically significant infection that manifests as refractory anemia during the posttransplantation period. The use of polymerase chain reaction for diagnosis is particularly helpful in immunosuppressed transplant patients who may fail to mount antibodies against PVB19 during active infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
226
1
21

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(256 citation statements)
references
References 85 publications
8
226
1
21
Order By: Relevance
“…[65][66][67] Some other viruses may also cause thrombocytopenia by various mechanisms, such as Epstein-Barr virus, human herpes virus-6, parvovirus B19. [68][69][70][71][72] CMV or human herpes virus-6 in post-alloBMT patients may also cause vascular endothelial injury, which could lead to development of thrombotic microangiopathy. 73 Cytokine-induced thrombocytopenia It is possible that similar mechanisms are responsible for the thrombocytopenia in infection and cGVHD.…”
Section: Immune-mediated Thrombocytopeniamentioning
confidence: 99%
“…[65][66][67] Some other viruses may also cause thrombocytopenia by various mechanisms, such as Epstein-Barr virus, human herpes virus-6, parvovirus B19. [68][69][70][71][72] CMV or human herpes virus-6 in post-alloBMT patients may also cause vascular endothelial injury, which could lead to development of thrombotic microangiopathy. 73 Cytokine-induced thrombocytopenia It is possible that similar mechanisms are responsible for the thrombocytopenia in infection and cGVHD.…”
Section: Immune-mediated Thrombocytopeniamentioning
confidence: 99%
“…5 Chronic anemia is well-recognized complication in approximately 39% of RTR, with erythropoietin-resistant anemia occurring in almost 9% of them. 8 PVB19 is capable of targeting erythroid progenitor cells in the bone marrow leading to a cessation in erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…If serology and PCR are negative but the clinical suspicion is high, examination of bone marrow specimen using immunohistochemical staining or in situ hybridization is helpful in establishing the diagnosis. 5 The main histopathological pictures of PVB19 infection of allograft kidney are thrombotic microangiopathy and collapsing glomerulopathy. [17][18][19] Reports have shown an elevation of plasma creatinine and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Parvovirus B19 has been associated with many complications after solid organ and allo-SCT. 3 Recently, Eid et al 4 reported on 98 patients who received a graft (allo-SCT 24%), with Parvovirus B19 infection. The hallmark of the infection is chronic anemia (98% of patients), with leucopenia and thrombocytopenia in almost one-third of the cases.…”
mentioning
confidence: 99%